2016
DOI: 10.1016/j.bbrc.2016.01.133
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-222-3p activity promoted osteogenic differentiation of hBMSCs by regulating Smad5-RUNX2 signal axis

Abstract: miRNAs are recently found playing important roles in osteogenesis. In this study, we identified that miR-222-3p decreased during osteogenic differentiation of human mesenchymal stem cells (hBMSCs) using Quantitative Real-Time Reverse Transcription PCR (qRT-PCR). Furthermore, we investigated the effect of miR-222-3p on osteogenic differentiation of hBMSCs. Inhibition of miR-222-3p function in hBMSCs using infection of lentiviruses carrying miR-222-3p specific inhibitor promoted expression of osteoblast-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 25 publications
4
33
0
Order By: Relevance
“…miR-210 and miR-378a promoted osteogenesis in rodent cells, 20,21 which contrasts the inhibitory effects observed in our study employing hBMSCs, whereas miR-34c and miR-146a inhibited osteoblastogenesis in rodent cells, 21,22 which is in agreement with our study. The remaining four were studied in human MSCs; miR-222, miR-31 (also in rats), and miR-138 inhibited osteoblastogenesis, 5,9,[23][24][25] which was consistent with our study, whereas miR-17 upregulated osteoblastogenesis, which is in contrast with our study. 26 These results show that some miRNAs are evolutionary conserved and play a similar role across species such as miR-31 and miR-34c, whereas other miRNAs, such as miR-210 and miR-378a, exhibit species specificity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…miR-210 and miR-378a promoted osteogenesis in rodent cells, 20,21 which contrasts the inhibitory effects observed in our study employing hBMSCs, whereas miR-34c and miR-146a inhibited osteoblastogenesis in rodent cells, 21,22 which is in agreement with our study. The remaining four were studied in human MSCs; miR-222, miR-31 (also in rats), and miR-138 inhibited osteoblastogenesis, 5,9,[23][24][25] which was consistent with our study, whereas miR-17 upregulated osteoblastogenesis, which is in contrast with our study. 26 These results show that some miRNAs are evolutionary conserved and play a similar role across species such as miR-31 and miR-34c, whereas other miRNAs, such as miR-210 and miR-378a, exhibit species specificity.…”
Section: Discussionsupporting
confidence: 90%
“…13,42 In accordance with this, recent studies have shown that inhibiting miR-222 enhanced osteogenesis in vitro and fracture healing in the femur of rats. 23,24 Cell-cycle regulation is essential for hBMSC self-renewal and growth, and this occurs through the inhibition of cell-cycle inhibitors such as CDKN1B and CDKN1A. 45 Here, we show that CDKN1B is inhibited by miR-222.…”
Section: Discussionmentioning
confidence: 72%
“…Smad5, Runx2 Increased in serum of aged patients, (77) and inhibits osteoblastogenesis in vitro in human mesenchymal stem cells. (80)…”
Section: Hsa-mir-20a-5pmentioning
confidence: 99%
“…A recently study demonstrated that miR-214 represses the osteogenic differentiation of MSCs by inhibiting the FGFR1/FGF signaling pathway [20]. Moreover, suppression of miR-222-3p activity promoted the osteogenic differentiation of hBMSCs through regulating the Smad5-RUNX2 signaling axis [21]. With the development of related studies, miRNAs could probably be applied in bone tissue engineering and disease therapy.…”
Section: Introductionmentioning
confidence: 99%